Two new species of Apobaetis Day, 1955 (Ephemeroptera: Baetidae) from Brazil - Cruz, Paulo Vilela; De-Souza, Marcia Regina (Zootaxa, 2014)
Apobaetis Day, 1955 species are known for their small size and preference for sandy stream substrate. Species which possess such habitat preference commonly possess long and slender legs and claws, but, in Apobaetis, the length of the tarsal claw rarely is so long that it exceeds the length of tarsus, occurring only in two species: A. lakota McCafferty, 2000 from USA and A. hamadae Cruz, Boldrini & Salles, 2011 from Brazil. In the present study, two new species with tarsal claws that exceed the length of the tarsi are described: Apobaetis pucupi sp. nov. from southeast Brazil and Apobaetis kethepiali sp. nov. from northernmost Brazil. Additionally, a new key for nymphs of Apobaetis is proposed.